Analisis Kualitas Fisik dan Risiko Kontaminasi Terhadap Kandungan Bakteriologis Pada Sumur Gali di Wilayah Kerja Dinas Kesehatan OKU 2021 - Fitri Suryani; Erma Gustina; Maria Ulfah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
The decline in the quality of clean water used by the community due to contamination of dug well water which allows the development of various types of bacteria. One of them is coliform bacteria. The formulation of the problem in this study is whether the physical factors and the risk of contamination can be known to be related to the bacteriological content of dug wells. This study aims to analyze the physical factors and risk of contamination of the bacteriological content of dug wells. The research design used was cross sectional. This research was conducted in the work area of the OKU District Health Office in 2021. The population in this study was dug wells that had been carried out by an Environmental Health Inspection (IKL) and a sample of 57 dug wells. The study was conducted from June 2021 to July 2021. The analysis was carried out using the chi square test with a significance level of p value 0.05. The results showed that there was no relationship between cloudiness (p value = 0.308), odor (p value = 0.308), taste (p value = 1,000), and color (p value = 0.568) on the bacteriological content of dug wells, and there was a relationship between risk of contamination (p value=0.048) on the bacteriological content of dug wells. The results of multivariate analysis showed that there was no dominant variable with bacteriological content in dug wells. The conclusion in this study was that there was no relationship between turbidity, odor, taste, and color variables with bacteriological content of dug wells. There is a relationship between the contamination risk variables and the bacteriological content of the dug wells. And there is no dominant variable affecting the bacteriological content of dug wells. This study suggests that the OKU district health office can improve public knowledge by way of health education and seminars, especially about the quality of dug wells and to the community in order to improve the physical condition of dug wells such as lips, floor walls, and sewerage for the high category while for the low category must be checked.